A gestão de recursos humanos nas Organizações Não Governamentais de cooperação para o desenvolvimento portuguesas : uma análise interpretativa exploratória - Marcos, Vanessa (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
In the light of the theoretical-empirical debate on the instrumentalization of volunteering and on the precarization of the labor market, in this article we problematize human resources management in Non- Governmental Development Organizations (NGDOs) regarding their higher and lower orientation to professionalization as an organizational strategy of efficiency and efficacy. Through data collected from a survey applied to 23 Portuguese NGDOs intentionally selected we present a general characterization of their paid workers and volunteers as well as an interpretative analysis of the human resources’ management practices.